Melatonin treatment of pre-veraison grape berries modifies phenolic components and antioxidant activity of grapes and wine - MENG,Jiang-Fei (2019)
Abstract A comprehensive investigation was conducted to determine the effects of exogenous melatonin treatment of pre-veraison grapes on phenolic components and antioxidants of grape berries and wine. The results showed an increase in the concentration of cyanin-3-O-glucoside, peonidin derivatives, and two flavanols [namely (+)-catechins and (−)-epicatechins] of grapes, as well as flavonols in both grapes and wine due to the application of melatonin. These compounds are derivatives of the catalysate of flavonoid 3’-hydroxylase (F3’H) in the flavonoid synthesis pathway of plants. It can be inferred that melatonin increased the activity of F3’H or expression of VvF3’H during grape berry maturation. In addition, two melatonin treatments of pre-veraison grape berries reduced the DPPH radical-scavenging ability and copper ion-reducing power of grapes and wine, whereas one melatonin treatment just reduced those in wine. This study will provide a practical strategy to change the phenolic composition of grapes and wine.